Strategies of effective low share businesses - Woo, Carolyny. Y.; Cooper, Arnold C. (Strategic Management Journal, 1981)
Abstract Previous research has suggested that low share market businesses have dismal prospects. This study examines low share businesses which are effective. In particular, it examines the product‐market choices and competitive strategies of effective low share businesses, comparing them with two control groups: effective high share and ineffective low share businesses. Data are drawn from PIMS data bases and hypotheses are tested using cluster analysis and discriminant analysis. Effective low share businesses are found to locate in stable rather than protected environments. Their competitive strategies are strongly characterized by selective focus on specific strengths.